Making it in real estate : starting out as a developer - McNellis, John (Washington, D.C : Urban Land Institute, 2020)
What does it take to be a successful real estate developer? Author John McNellis tells you how, sharing practical tips and advice from his wealth of experience over 35 years in real estate development. Like meeting with a mentor over coffee, McNellis entertains with witty anecdotes, and wisdom on how to take advantage of opportunities and avoid pitfalls. Offering humorous insights, the book covers the ins and outs of how to get financing, working with architects, brokers, and other professionals, how to make a good deal, and win approval for your project. This updated and expanded edition includes 25 new chapters covering leadership, investment decisions, the regulatory environment, and guidance on how to survive a downturn.
Front Cover -- Title Page -- Copyright -- About the Author -- Contents -- Preface -- Part 1: Making It in Real Estate -- 1. Quit Your Job? -- 2. Doing It on the Side -- 3. Playing Small Ball -- 4. Specialize or Die -- 5. Bromancing the Deal -- 6. Size Matters -- 7. Buying It Right -- 8. Desperately Chasing Yield -- 9. Liquid Assets -- 10. A Little Help from My Friends -- 11. Fickle Shades of Green -- 12. Autographing the Deal -- 13. The Politics of It All -- 14. Decked by City Hall? -- 15. Sell versus Hold -- 16. Lies, Damn Lies, and the IRR -- 17. Working without a Net Worth 18. Monogamy and Its Downside -- 19. Let Us Now Praise Famous Architects -- 20. General Contractor Relativity -- 21. Sex, Lies, and Off-Market Deals -- 22. Do As I Say -- 23. The Back of a Napkin -- 24. No Partners, No Problems -- 25. The "NTM" -- 26. Understating Your Net Worth -- 27. Leaseholds: Buy 'Em Where They Ain't -- 28. Your Empire: Build It or Buy It? -- 29. The 1031 Exchange: Panacea or Placebo? -- 30. The Only Free Cheese Is in a Mouse Trap -- 31. Game of Phones -- 32. Winter Is Coming -- 33. Winter Is Here -- 34. There's No Place Like Home -- 35. Investing in Accidental Assets 36. Retail's Wholesale Risks -- 37. Environmental Contamination: Hazardous to Your Health? -- 38. A Sod Roof Too Far -- 39. Money -- 40. Abandon All Hope -- Part 2: Making It in Life -- 41. How to Keep Friends and Influence No One -- 42. Commencement Address -- 43. Your Obituary -- 44. Seeing the Forest for the Trees -- 45. In Memoriam: James J. Curtis III -- 46. Postscript -- Glossary: Real Estate Jargon Demystified.
Keywords: REAL ESTATE BUSINESS -- MANAGEMENT